Prevalensi dan Serovar Penyebab Leptospirosis pada Domba di Kabupaten Kulon Progo - Guntari Titik Mulyani; Eko Sulistyadi; Antoni Kirwanto; Haryadi Haryadi; Ambar Widuri; Tri Atmojo; Anis Pramundari (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Leptospirosis is a zoonotic disease, caused by Leptospira interrogans. A source of transmission in human leptospirosis are rodents, livestock, pets and wild animals. The prevalence of leptospirosis in cattle soon after theoutbreak of leptospirosis in humans that occurs in Kulon Progo district in 2011, reached 3.4% by the various serovar Leptospira. Breeding conditions of the people who still puts cattle and sheep in a single environment which enables transmission of leptospirosis in cattle. The purpose of this study was to determine the prevalence of leptospirosis and identify serovar caused of leptospirosis in sheep in Kulon Progo. A total of 60 sheep were done blood collection from the jugular vein 5 ml, serum was separated for leptospirosis examination with Microscopic Aglutination Test (MAT) which conducted at the Research Center for Veterinary Science, Bogor. Microscopic Aglutination Test carried out on various Leptospira serovar, namely: chterohaemorrhagiae, Javanica, Celledoni, Ballum, Pyogenes, Cynopeteri, Rachmati, Auatralis, Pomona, Canicola, Grippotyphosa, Bataviae, Hardjo, and Tarrasovi. Leptospirosis prevalence rate was calculated by dividing the result by the number of MAT positive samples examined. Serovar types that give a positive agglutination result was serovar that caused leptospirosis in sheep. The results showed that two samples were positive against antigen serovarIchterohaemorrhagiae. Based on these results can be concluded that the prevalence of leptospirosis in sheep in Kulon Progo district were 3.3%. The cause of leptospirosis in sheep in Kulon Progo was Leptospira interrogansIchterohaemorrhagiae serovar.